Using space - today and tomorrow. proceedings of the XXVIII International Astronautical Congress, Prague, 25 September - 1 October 1977 /: proceedings of the XXVIII International Astronautical Congress, Prague, 25 September - 1 October 1977. Communications Satellite Symposium : Volume 2, ([2015?]) - Unknown
No abstract available